Pengaruh Persepsi E-Service Quality pada Layanan Pemesanan Tiket Kereta Api Terhadap Kepuasan Mahasiswa Pengguna Traveloka - Haqimah Shafa Salsabilla; Lathifah Zakiyatuz Zahra; Milladyah Laila Sari; Khairani Zikrinawati; Zulfa Fahmy (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
. This research was conducted based on the increasing use of the internet use in Indonesia and the opportunities for online train ticket sales namely e-ticketing and the possibility of having a relationship with customer satisfaction. This research aims to determine the effect of perceived e-service quality on train ticket booking services on students satisfaction using Traveloka. This research used a quantitative research method by distributed questionnaires online. This research used a sampling technique namely non-probability sampling with purposive sampling. Data collection was done by spreading the questionnaires to related respondents. The population in this research are 114 students from various universities who have booked train tickets at Traveloka. The result of this research indicated that there is a positive and significant effect between perception of e-service quality in train ticket booking services on students who use Traveloka satisfaction